EFFECT OF PHYSIOLOGICAL AGE AND GROWTH REGULATORS ON CALLUS BROWNING OF COCONUT ENDOSPERM CULTURE IN VITRO - SUKAMTO*, LAZARUS AGUS (BIOTROPIA, 2024)
<!-- [if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!-- [if gte mso 9]> <![endif]--> The possibility of physiological age and growth regulators affecting callus browning of coconut endosperm was investigated. Solid endosperm explants of four coconut fruits from same brunches of two coconut cultivars â€œSamoan Dwarfâ€ were grown on modified Murashige and Skoog (MS) formula with addition of 10 mg l-1 putresine, 2.50 g l-1 activated charcoal (AC), 1.70 g l-1 phytagel, 0, 10-6, 10-5, 10-4, 10-3 M 2,4-dichlorophenoxyacetic acid (2,4-D) or 4-amino-3,5,6-trichloropicolinic acid (Picloram) Â combined with 10-5M 6-benzylaminopurine (BA). Callogenesis occurred on 98.83% of explants. Â Callus browning between different physiological ages (antipodal and micropylar tissues) of coconut endosperm at Â 9, 26 and 31 weeks of culture (WOC) was significantly different, but not at 16 and 21 WOC. Auxins of 2,4-D and Picloram did not affect significantly callus browning of endosperm cultures. Auxin doses at 10-6, 10-5, and 10-4M decreased significantly callus browning at 9 and 16 WOC, respectively, Â but at 10-6M Â browning was less significant compared to Â other doses at Â 21 WOC. Auxin dose at 10-3 M caused Â less significant Â browning compared to Â other doses at Â 31 WOC. The addition of BA decreased significantly callus browning at Â 9 WOC , but did not affect callus browning thereafter. Key words: Coconut, in vitro, Picloram, 2,4-D, BA Â 